MicroRNAs as a diagnostic tool for heart failure and atrial fibrillation. (April 2016) - Weckbach, Ludwig T; Grabmaier, Ulrich; Clauss, Sebastian; Wakili, Reza
Highlights: miR423-5p discriminated patients with HF from those with other causes of dyspnea. miRNA-related pathophysiological mechanisms of AF were shown for miR-21 and miR-29b. No consistent evidence for one particular miRNA as biomarker could be provided. No harmonized methodological standards for the assessment of miRNAs in the blood exist. Larger trials to establish miRNAs as clinically usable biomarkers are required. Abstract : MicroRNAs (miRNAs) are small non-coding RNAs, which are directly involved in the regulation of post-transcriptional gene expression. Their biological function represents a repression of protein expression of the targeted messenger-RNA(s). Expression of several miRNAs is somehow tissue-specific or cell-specific and their expression pattern can reflect an underlying pathophysiological condition. Beyond this biological function their role as potential biomarkers has been emerged in the past years. This was based on the fact that miRNAs can be detected in blood samples (serum or plasma) in a surprisingly stable form, by contrast to mRNAs. This fact made miRNAs interesting candidates for biomarkers providing information with respect to a potentially ongoing pathophysiological condition and could thereby have an impact on specific treatment strategies in patients. In this review we try to provide an overview of the potential role of miRNAs as a diagnostic tool in atrial fibrillation and heart failure patients taken different methodological aspects and distinct type of patients into account.